Crew and natives, possibly Siberian Eskimos, on board ship, probably Aleutian Islands, approximately 1899 - Warner, Arthur Churchill, 1864-1943 (1899)
This photograph was probably taken aboard ship somewhere in the Russian Aleutian Islands. Warner [2103] Filed in Alaska series.